Un programme d’assurance-inondation pour le Québec - Viau, Robert (Assurances, 1985)
Mr. Robert Viau has prepared an article on a subject which has rarely been dealt with in the past. It is of particular interest to property owners threatened by spring flooding, caused by the swell of water coming from the distant regions where rivers find their source. There are already some insurance policies, described as "all risks", which cover flooding subject to a very precise wording. In Eastern Canada, such coverage is not widely available, and then only subject to strict conditions. Mr. Viau studies the main elements for a program of flood insurance to protect the insured. Flooding is not, after all, an uninsurance risk. It can be covered, but only subject to stringent conditions and where there is a general will to reduce the risk.